Effect of PDYN rs2281285, rs2235749 and rs910080 gene polymorphisms on the intensity of depression symptoms and negative craving in heroin addicts - Kaya-Akyüzlü, Dilek; Özkan-Kotiloğlu, Selin; Yalçın-Şahiner, Şafak; Ayaz, Nagihan (Archives of Biological Sciences, 2021)
Paper decription: The effects of prodynorphin (PDYN) gene haplotypes containing polymorphisms rs910080, rs2281285, rs2225749 (SNPs) on heroin dependence risk were examined for the first time. Gene polymorphisms were genotyped (PCR-RFLP) in 100 heroin addicts and 108 healthy controls. Craving and depressive symptoms were measured by the Substance Craving Scale and Beck Depression Inventory-II, respectively. Individuals with the AAA haplotype are more prone to heroin dependence; rs2281285 and rs2225749 affect the intensity of depressive symptoms; rs2225749 contributes to induction of negative craving. These findings show the association of PDYN haplotypes composed of rs2281285, rs2235749 and rs910080 with heroin dependence. Abstract: The present study was undertaken to explore whether prodynorphin (PDYN) polymorphisms have an effect on the intensity of depressive symptoms and negative craving in heroin addicts in a sample of 100 heroin addicts and 108 controls. PDYN rs2281285, rs2225749 and rs910080 polymorphisms were analyzed by PCR-RFLP. Craving and the intensity of depressive symptoms were measured by the Substance Craving Scale and the Beck Depression Inventory-II, respectively. A significant association between depression severity and PDYN rs2281285 (P=0.026) and rs2225749 (P=0.038) polymorphisms was detected. PDYN rs2225749 variation showed a trend association with increased negative craving (P=0.066). We also examined the associations between heroin dependence and PDYN rs2281285, rs2225749 and rs910080 gene polymorphisms at the gene and haplotype levels. The AAA haplotype was more frequent in heroin addicts and shown to be significantly associated with increased risk for heroin dependence (OR, 8.922; 95% CI, 1.116-71.313; P<0.05). PDYN rs2281285 and rs2225749 variations affected the intensity of depressive symptoms, and PDYN rs2225749 polymorphism may contribute to the induction of negative craving in heroin addicts. Haplotype analysis revealed for the first time that addicts with the AAA haplotype of PDYN gene may be more prone to heroin dependence.